Essays in Honour of Yigael Yadin - Vermes, Geza (1983)
$42.50; 3-18: A. Ben-Tor, The Relations between Egypt and the Land of Canaan during the Third Millennium B.C.; 55-59: R. M. Good, Metaphorical Gleanings from Ugarit; 61-70: W.G.Lambert, Booty from Egypt?; 71-79: A.Malamat, 'Silver, Gold and Precious Stones from Hazor': Trade and Trouble in a New Mari Document.